Analisis Penerapan Media Pembelajaran Interaktif Berbasis Google Classroom dalam Menyongsong Era Revolusi Industri 4.0 Terhadap Hasil Belajar Matematika Siswa - Ratnasari Ratnasari; Nikmah Nurvicalesti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
Unlimited use of the internet in the era of the Industrial Revolution 4.0 due to technological developments causes everything to be limitless. It is believed that this era will disrupt many fields, without exception in the field of Indonesian language and literature education. Aligning learning at a practical level that is adapted to the curriculum construct becomes the first focus of homework competition in the field of education. Prioritizing 'soft skills' and 'transversal skills', life skills, and invisible skills related to certain work and academic fields. This article uses a research method. This article is written using a descriptive exploratory approach using a literature study, where data is collected to see the real situation that is happening now. These results provide an overview of how the process of integrating digital technology in learning mathematics. Practicing student discipline is also evident in this study. Increased knowledge of students at the cognitive level is not influenced by the initial ability of students, but is influenced by the ability of teachers as creators to create a fun learning process that can have an impact on improving student learning outcomes themselves.